In-Vitro Î±-Glucosidase Inhibitory Activities of Muntingia Calabura Linn. - I.I. Nor Azman, N; Hashim, N; Ahmad, R (International Journal of Engineering and Technology, 2019)
Muntingia calabura Linn. also known locally as â€œceri kampungâ€ is a plant of the family Elaeocarpaceae. The plant has been reported to possess several medicinal properties including reducing high blood pressure, lowering cholesterol level and controlling Type 2 diabetes. Type 2 diabetes is usually related to postprandial hyperglycemia, which is related to the rise of blood sugar level after a meal. This condition can be controlled by Î±-glucosidase inhibitors which inhibit the enzyme from catalyzing the liberation of glucose from carbohydrates in the digestive tract. Despite many biological studies reported for the plant, its antidiabetic potential has not been widely explored. Thus the aim of this study was to find potential Î±-glucosidase inhibitors from 16 extracts of M. calabura as a therapeutic approach in decreasing postprandial hyperglycemia. The hexane (Hx), ethyl acetate (Ea), 75% ethanol (Et) and aqueous (Aq) extracts of four parts (fruit, leaf, stem and root) of M. calabura (collected from Bangi, Selangor) were screened for their a-glucosidase inhibitory activities at 50.00, 25.00, 12.50, 6.25, 3.13, 1.56 and 0.78 ppm prepared via two-fold serial dilution against the positive control, acarbose. The aqueous leaf (AqL) and root extracts (AqR) exhibited very strong activities with IC50 values of 0.15 and 0.41 Âµg/mlÂ while the other extracts showed strong to moderately strong activities with IC50 values ranging from 1.83-11.66Â Âµg/ml against acarbose (4.3 Âµg/ml).Â